2018
DOI: 10.1177/0954407018776743
|View full text |Cite
|
Sign up to set email alerts
|

Model-based computational intelligence multi-objective optimization for gasoline direct injection engine calibration

Abstract: For modern engines, the number of adjustable variables is increasing considerably. With an increase in the number of degrees of freedom and the consequent increase in the complexity of the calibration process, traditional design of experiments–based engine calibration methods are reaching their limits. As a result, an automated engine calibration approach is desired. In this paper, a model-based computational intelligence multi-objective optimization approach for gasoline direct injection engine calibration is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…32 The output value of Sugeno-type fuzzy controller is transformed to a constant value directly by fuzzy rules without the need to calculate the weighted average of output membership functions, which allows the Sugeno-type fuzzy controller to perform more efficiently for realtime implementation. Figures 2 and 3 give the simplest membership functions for input and output signals of the Sugeno-type fuzzy controller which are defined over [21,1] First of all, input signals X 1 (k) and X 2 (k)are normalized by scaling them with K i and K p , respectively. Then, a set of fuzzy decision rules relating inputs to the output are constructed as Table 1 shows.…”
Section: Structure Of the Pi-like Fkbcmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The output value of Sugeno-type fuzzy controller is transformed to a constant value directly by fuzzy rules without the need to calculate the weighted average of output membership functions, which allows the Sugeno-type fuzzy controller to perform more efficiently for realtime implementation. Figures 2 and 3 give the simplest membership functions for input and output signals of the Sugeno-type fuzzy controller which are defined over [21,1] First of all, input signals X 1 (k) and X 2 (k)are normalized by scaling them with K i and K p , respectively. Then, a set of fuzzy decision rules relating inputs to the output are constructed as Table 1 shows.…”
Section: Structure Of the Pi-like Fkbcmentioning
confidence: 99%
“…Global optimization algorithms are widely used to resolve nonlinear optimization problems, because they are able to find globally optimal results instead of resulting in multiple locally optimal results. [18][19][20][21] Metaheuristic algorithm is one of the most well-known global optimization methods. 22,23 And swarm intelligence algorithm, such as particle swarm optimization (PSO) algorithm, is one of the main categories of metaheuristic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…A B Feng Wu wufeng_my@mail.nwpu.edu.cn working condition is often described by a number of parameters depending on the actual usage of engine, such as the speed. Traditional calibration process is achieved by manually changing the engine parameters, simulating its state under different working conditions, comparing its states on engine maps [23], and repeating the above steps until the states are closed to some desired states. Figure 1 illustrates the manual process of adjusting engine parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The calibration process is usually time-consuming and highly relies on the human knowledge. Ma et al [22,23] proposed a multiobjective optimisation approach to automate the gasoline direct injection engine calibration process, in which five engine parameters were adjusted under four cases and three evaluation criteria were considered for each case. However, some of the engines, such as aero-engines, are controlled by dozens of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the multi-objective optimization using neural networks is a promising approach to find optimum solutions for engine valve-timing. Ma et al 25 presented a multi-objective optimization strategy using a mean-value model of a gasoline direct injection engine to predict fuel consumption and soot emissions together with the Strength Pareto Evolutionary Algorithm (SPEA). Their results showed an improvement of 3.2% of the indicated specific fuel consumption (ISFC) with the optimized engine control parameters.…”
Section: Introductionmentioning
confidence: 99%